Catalisadores de Cr/ZrO2 promovidos com metais alcalinos ou alcalinos terrosos para a desidrogenação oxidativa do propano com CO2 - Oliveira, João Pedro Bueno de (Universidade Federal de São Carlos, 2021)
Propene is used as a raw material for thermoplastic resins, adhesives and acrylic derivatives, being obtained mainly by steam cracking naphtha and natural gas. However, the oxidative dehydrogenation of propane reaction using carbon dioxide as a moderate oxidant (ODP-CO2), has been studied as an environmentally more interesting proposal. Chromium and zirconia-based catalysts are widely applied in ODP, however, they have major limitations due to the need for catalytic regeneration resulting from the formation of coke on the surface. The addition of alkali metals (AM) or alkaline earth metals (AEM) in chromium catalysts shows promise for ODP, increasing conversion, selectivity and stability, in addition to decreasing the amount of coke on the catalytic surface, due to changes in the acid/basic characteristics of the catalyst surfaces. In general, this paper seeks to evaluate the effect of the addition of AM or AEM on the catalytic properties of monoclinic Zr-supported Cr catalysts applied to ODP-CO2, advancing the understanding of the role of CO2 as a moderate oxidizing agent in the reaction. Thus, two monoclinic zirconia supports were synthesized using hydrothermal (ZrH) and precipitation (ZrP) methods, which have similar crystallinities and low specific areas, but with different pore structures. The addition of chromium to the supports did not change the crystalline phase, but reduced its specific area and pore volume; for ZrH there was the formation of Cr+6 oxides of easier reduction, while in ZrP, mainly Cr+6 and Cr+5 oxides of more difficult reduction were formed. The promotion of Cr/Zr catalysts with AM or AEM did not change their crystallinity and increased the amount of Cr+6 species, however reducible at higher temperatures. Furthermore, the Cr/Zr catalysts promoted by AM or AEM have different populations of basic sites according to the amount and type of metal added. The addition of AM to Cr/Zr catalysts was able to suppress the formation of by-products and coke, especially with the addition of sodium, providing reasonable stability to the catalysts promoted for 300 minutes. Although this effect was more evident on the catalyst supported on zirconia H (0.5% Na-Cr/H), the best catalytic performance was obtained for 0.5% Na-Cr/P compared to 10Cr/P, which also revealed outstanding CO2 conversion, indicating favoring of DOP-CO2 from 600°C to 700°C. However, the favoring of the DOP-CO2 route was more evident by the addition of AEM to Cr/Zr catalysts, mainly 0.5% Ca-Cr/P, although the same effect of suppression of the formation of by-products and of coke.
Cr/ZrO2 catalyst promoted with alkaline or earth alkaline metals for the oxidative dehydrogenation of propane with CO2
Keywords: Cromo; Zircônia; Metais alcalinos; Metais alcalinos terrosos; Desidrogenação oxidativa; CO2; Chrome; Zirconia; Alkali metals; Alkaline earth metals; Oxidative dehydrogenation; ENGENHARIAS::ENGENHARIA QUIMICA::PROCESSOS INDUSTRIAIS DE ENGENHARIA QUIMICA